2021
DOI: 10.3389/fneur.2021.610840
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Deep Brain Stimulation in the Subthalamic Nucleus on Neurocognitive Function in Patients With Parkinson's Disease Compared With Medical Therapy: A Meta-Analysis

Abstract: Background: DBS has been shown to significantly affect motor symptoms in Parkinson's disease (PD). However, some studies have suggested that it may have adverse effects on patients' neurocognitive function. To clarify this operation's effect on neurocognitive function, we collected studies containing neurocognitive function evaluation for qualitative and quantitative analysis.Methods: We searched relevant clinical studies through Pubmed and Embase databases and extracted and sorted out information such as samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 76 publications
3
17
0
Order By: Relevance
“…A prior meta-analysis and an observational study involving solely STN-DBS patients reported no significant differences in processing speed (Castelli et al, 2006;Parsons et al, 2006), while one study found that STN-DBS improves reaction times (Temel et al, 2006). Similar results were found in two recent meta-analyses and a controlled clinical trial comparing STN-DBS and BMT control patients (Williams et al, 2011;Xie et al, 2016;Wang et al, 2021). Slightly worse performance on testing has been found in STN-DBS patients compared to GPi-DBS patients in several studies (Combs et al, 2015;Tan et al, 2016;Wang et al, 2016).…”
Section: Processing Speedsupporting
confidence: 52%
See 4 more Smart Citations
“…A prior meta-analysis and an observational study involving solely STN-DBS patients reported no significant differences in processing speed (Castelli et al, 2006;Parsons et al, 2006), while one study found that STN-DBS improves reaction times (Temel et al, 2006). Similar results were found in two recent meta-analyses and a controlled clinical trial comparing STN-DBS and BMT control patients (Williams et al, 2011;Xie et al, 2016;Wang et al, 2021). Slightly worse performance on testing has been found in STN-DBS patients compared to GPi-DBS patients in several studies (Combs et al, 2015;Tan et al, 2016;Wang et al, 2016).…”
Section: Processing Speedsupporting
confidence: 52%
“…The cognitive domain of memory was assessed in numerous studies, with conflicting results. Meta-analyses generally point to a slight decline in working and general memory mostly in STN-DBS patients compared to GPi-DBS and BMT patients (Combs et al, 2015;Wang et al, 2016;Xie et al, 2016), with only a study by Wang et al (2021) showing no significant changes, but a trend of worsening in STN-DBS patients compared with BMT. More conflicting findings are found in randomized controlled trials and controlled clinical trials, with slightly fewer studies finding worsening of memory and intact learning (Smeding et al, 2006;York et al, 2008;Weaver et al, 2009Weaver et al, , 2012Rothlind et al, 2015), and no changes compared to BMT controls or between STN-DBS and GPi-DBS patients (Gironell et al, 2003;Zangaglia et al, 2009;Castelli et al, 2010;Daniels et al, 2010;Merola et al, 2011Merola et al, , 2014Sáez-Zea et al, 2012;Tramontana et al, 2015;Boel et al, 2016;Foki et al, 2017).…”
Section: Memory and Learningmentioning
confidence: 97%
See 3 more Smart Citations